Development of a prototype autonomous inspection robot for offshore riser cables. (1st August 2022) - Gotts, Christopher; Hall, Benjamin; Beaumont, Oliver; Chen, Ziyang; Cleaver, William; England, James; White, David; Thornton, Blair
Abstract: The motion and large environmental loads experienced by riser cables connected to floating offshore wind turbines put them at higher risk of failure than grounded sections of cable. We propose an Autonomous Riser Inspection System (ARIS) to facilitate regular inspection of riser cables for early fault detection and gathering engineering data to improve future cable design. Novel robotic methods for automatic attachment, traversal and inspection of cables are described. We develop the sensing and intelligent processing needed to (i) enable autonomous traversal and position estimation, and (ii) gather information about the state and condition of riser cables. Information from an array of cameras and electric actuator current monitoring allows autonomous navigation around obstacles and identifying the end of the inspection. A visual processing algorithm identifies damage to the surface of the cable and sensing methods are developed to measures the cable catenary, where methods to estimate the robot's position along the cable are developed to contextualise and efficiently re-locate observations. Technology concepts are verified through a combination of dry, lab-based experiments using a full-scale prototype and simulations. The results provide proof of concept that requirements for untethered, autonomous riser cable inspection can be met by the proposed system. Highlights: An autonomous robotic method for offshore wind riser cable inspection is proposed. Automatic attachment, traversal and visual inspection techniques are developed. Obstacle avoidance, position estimation and catenary profiling methods developed. Experiments demonstrate novel technology concepts using a full-scale prototype.